ANALISIS PERTUMBUHAN EKONOMI INKLUSIF KABUPATEN GORONTALO - Imbran, Harijono; Alkatiri, Ramlah; Machmud, Fransiska (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2025)
This study aims to determine the inclusive economic growth of Gorontalo Regency. This study uses a quantitative approach using secondary data from both the Gorontalo Regency Central Statistics Agency (BPS) and the Gorontalo Regency Regional Development Acceleration Agency. The analytical tools used are economic growth and the Inclusive Growth Index (IGI). The results show that Gorontalo Regency's economic growth from 2023 to 2024 has demonstrated inclusiveness in reducing poverty, as reported by the 2024 BPS report, where the poverty rate decreased by 1.05%. Population significantly influences economic growth in Gorontalo Regency from 2020 to 2024. The dependency ratio partially significantly influences economic growth in Gorontalo Regency from 2020 to 2024.